2022
DOI: 10.1002/mame.202200276
|View full text |Cite
|
Sign up to set email alerts
|

Development of a Self‐Adhesive Oleogel Formulation Designed for the Slow Release of Semiochemicals

Abstract: Oleogels have been widely studied as delivery matrices for lipophilic compounds. Despite their potential, oleogels are underexplored for the formulation and release of semiochemicals for insect behavior manipulation strategies. An ethylcellulose-candelilla wax-oleogel as a suitable carrier for the slow release of volatile semiochemicals, employing the sesquiterpene 𝜷-caryophyllene as a model substance is presented. A current drawback of ethylcellulose oleogels is the high temperature needed during the oleogel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 83 publications
(145 reference statements)
0
3
0
Order By: Relevance
“…The presence of very high amounts of oleogel can be the reason for this. It has been previously reported that oleogels form strong interactions with the interacting surfaces, thereby promoting adhesion [54].…”
Section: Texture Analysis Of Doughmentioning
confidence: 99%
“…The presence of very high amounts of oleogel can be the reason for this. It has been previously reported that oleogels form strong interactions with the interacting surfaces, thereby promoting adhesion [54].…”
Section: Texture Analysis Of Doughmentioning
confidence: 99%
“…[14][15][16][17][18] Among them, the dissolution DOI: 10.1002/mame.202300361 of poorly water-soluble drugs and their related controlled release profiles are drawing increasing attention. [19][20][21][22] Particularly, the fast or pulsatile release, one type of ratecontrolled release profile (Figure 1), has the advantages of rapid release for achieving a rapid therapeutic action for many diseases such as fever, aches, and emotional irritability. [23][24][25] During the past three decades, the giant progress of nanoscience and nanotechniques has provided many useful strategies for enhancing the dissolution and effective delivery of poorly water-soluble drugs.…”
Section: Introductionmentioning
confidence: 99%
“…[ 14–18 ] Among them, the dissolution of poorly water‐soluble drugs and their related controlled release profiles are drawing increasing attention. [ 19–22 ] Particularly, the fast or pulsatile release, one type of rate‐controlled release profile ( Figure ), has the advantages of rapid release for achieving a rapid therapeutic action for many diseases such as fever, aches, and emotional irritability. [ 23–25 ]…”
Section: Introductionmentioning
confidence: 99%